Kinetics of Myristic Acid Following Accidentally Induced Septic Response - Zazula, Roman; Průcha, Miroslav; Pehal, František; Dryahina, Kseniya; Moravec, Michal; Müller, Martin; Nejtek, Tomáš (Prague medical report, 2019)
Myristic acid was identified as a metabolite with the highest diagnostic sensitivity and specificity in the metabolome of patients with bacteraemia. Subsequently, its significant decrease was observed in patients in septic shock not responding to treatment. In our study we have captured myristic acid serum level kinetics in 96 hours following accidental intravenous self-administration of eubiotic Hylak forte causing infection-like systemic inflammatory response syndrome (SIRS). To our knowledge, this is the first time the kinetics of myristic acid levels is presented in a septic patient. Myristic acid was evaluated in comparison with other inflammatory biomarkers and with its level in a control group of healthy subjects. Myristic acid levels during septic response were significantly elevated in comparison with the control group. The peak level was recorded almost immediately after the insult with a gradual decrease within 96 hours. Myristic acid appears to be a promising biomarker in sepsis diagnostics, further research by our group into this topic is ongoing.
Keywords: Shock, Septic; Myristic Acid; Myristic acid; Kinetics; sepse; Inflammation; Humans; biologické markery; Syndrome; lidé; syndrom; Biomarkers; septický šok; Sepsis; kinetika; zánět; kyselina myristová